THE USE OF ENGLISH GRAMMAR APPLICATION TO IMPROVE THE STUDENTS’ WRITING IN RECOUNT TEXT AT SMAN 1 TANJUNG - Bina, Risa Masdania Kartika; Misrita, Misrita; Perdana, Indra (Journal Compound: Improving the Quality of English Education, 2021)
The objective of the study aims to effect examining of English Grammar Application for improving the students’ writing in recount text in the tenth grade of SMAN 1 Tanjung. The research applied quantitative approch and used pre experimental design. The population of this research students of X class consist 202 students of SMAN 1 Tanjung in academic year 2021/2022 and the Sample was X LM of English (Lintas Minat). And the sample research was taken as the sample using stratified sample. The data was collected by using written test. To analyze data, the researcher used the formula t test and effect size as procedure of analyze data. The result of this research showed that the research conducted effect size formula. The research got 0.9. this is the value of effect size level. Refer to the table of interpreting of effect size. This value 0.9 was > 0.5. so the effect size of using English Grmmar Application in learning Recount text has strong Effect.